C-Glycoside metabolism in the gut and in nature: Identification, characterization, structural analyses and distribution of C-C bond-cleaving enzymes - Takahiro Mori (Nature Portfolio, 2021)
In C-glycosides the sugar moiety is linked through a carbon-carbon bond to the non-sugar moiety, which can be cleaved by intestinal microbes. Here, the authors use bioinformatics analysis to identify C-glycoside deglycosidase enzymes in intestinal and soil bacteria, biochemically characterise them and determine their structures and probe catalytic important residues in mutagenesis experiments.